2021
DOI: 10.1038/s41467-021-21094-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of nodulation in Aeschynomene evenia uncovers mechanisms of the rhizobium–legume symbiosis

Abstract: Among legumes (Fabaceae) capable of nitrogen-fixing nodulation, several Aeschynomene spp. use a unique symbiotic process that is independent of Nod factors and infection threads. They are also distinctive in developing root and stem nodules with photosynthetic bradyrhizobia. Despite the significance of these symbiotic features, their understanding remains limited. To overcome such limitations, we conduct genetic studies of nodulation in Aeschynomene evenia, supported by the development of a genome sequence for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 65 publications
2
66
0
Order By: Relevance
“…In particular, el Zahar Haichar et al (2014) and Wheatley et al (2020) identified a 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranosyl 5 -monophosphate in the roots of legumes, a substance able to supplement the rhizobial purine biosynthesis mutants during growth in the rhizosphere. Further, nodulation is controlled by the SHR-SCR module for inducing cortical cell division that is regulated by the nodule inception (NIN) transcription factor, the transcription of which is activated by rhizobial Nod factors via the CSSP (Dong et al, 2021;Quilbé et al, 2021). After nodule establishment, the plant exploits nodule transfer cells to sense the environmental nitrate status, to regulate plasticity of nodule development, by specifically expressing transporters of the NFP (NRT1/PTR FAMILY) .…”
Section: Symbiosismentioning
confidence: 99%
“…In particular, el Zahar Haichar et al (2014) and Wheatley et al (2020) identified a 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranosyl 5 -monophosphate in the roots of legumes, a substance able to supplement the rhizobial purine biosynthesis mutants during growth in the rhizosphere. Further, nodulation is controlled by the SHR-SCR module for inducing cortical cell division that is regulated by the nodule inception (NIN) transcription factor, the transcription of which is activated by rhizobial Nod factors via the CSSP (Dong et al, 2021;Quilbé et al, 2021). After nodule establishment, the plant exploits nodule transfer cells to sense the environmental nitrate status, to regulate plasticity of nodule development, by specifically expressing transporters of the NFP (NRT1/PTR FAMILY) .…”
Section: Symbiosismentioning
confidence: 99%
“…In L. japonicus and M. truncatula , LjEPR3 and MtLYK10 commit essential functions in rhizobium infection, whereas in Parasponia the orthologous gene is pseudogenized. Earlier studies showed that also in the legume Aeschynomene evenia the LjEPR3/MtLYK10 orthologous gene is absent [ 18 ]. However, this species possesses a close paralog, which possibly evolved as a result of a legume-specific duplication event and that may commit a similar function [ 9 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Legumes also offer advantages in utilisation as livestock feed and a source of income to small-scale farmers (Reddy et al, 2012). They enhance sustainable agriculture due to their nitrogen-fixing ability, limiting the use and impact of inorganic nitrogen fertilisers (Considine et al, 2017;Quilb e et al, 2021). With climate change affecting global agriculture, orphan legumes are alternatives for crop cultivation and utilisation (Murthy and Paek, 2021).…”
Section: Introductionmentioning
confidence: 99%